นาโนคอมโพสิตของเอ็มซีเอ็ม-48 อนุภาคระดับนาโนเมตรของเหล็กออกไซด์ อนุภาคระดับนาโนเมตรของทองแดงและไทเทเนียมไดออกไซด์ เป็นตัวเร่งปฏิกิริยาเชิงแสงแม่เหล็กในปฏิกิริยาอิพอกซิเดชันของสารประกอบอัลคีน - อจิรวดี สุวรรณจันทร์ (จุฬาลงกรณ์มหาวิทยาลัย, 2017)
Nanocomposites of MCM-48, iron oxide nanoparticle, copper nanoparticles and TiO₂ were synthesized for photocatalytic epoxidation of alkene in comparison with the composites with only copper nanoparticles or TiO₂ incorporated. The catalysts were characterized using Fourier transform infrared spectroscopy (FT-IR), X-ray diffractometry (XRD), surface analysis, inductively coupled plasma optical emission spectroscopy (ICP-OES), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The composited catalysts were in a spherical shape with a diameter of 400 nm, showed superparamagnetic character and comprised 0.62% by weight of Cu and 1.28% by weight of Fe₃O₄. The catalysts were tested for photo-epoxidation of styrene using tert-butyl hydroperoxide as an oxidant. The Cu-TiO₂-Fe₃O₄@MCM-48 showed slightly different of %yield and %conversion under ambient light, visible light and UV light condition. The most active composited catalyst was Cu-Fe₃O₄@MCM-48 showing high catalytic performance with 33% yield and 100% conversion under ambient light.